2016
DOI: 10.1016/j.juro.2015.09.072
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Cell Cycle Progression Test on Physician and Patient Treatment Selection for Localized Prostate Cancer

Abstract: The cell cycle progression test has a significant impact in assisting physicians and patients reach personalized treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 23 publications
0
32
0
2
Order By: Relevance
“…y Shore y cols., en 2014 y 2015 respectivamente, mostraron que el uso de Prolaris, cambió la conducta del tratamiento, evidenciando una importante reducción en manejo con intención curativa, 49,5% de cirugía, 29,6% de radioterapia en el estudio de Shore y un cambio en la conducta de tratamiento 47,8%, incluyendo tanto cirugía como radioterapia, en el estudio de Crawford. 13,14 En cuanto a los alelos de riesgo para cáncer de próstata, los resultados entre los diferentes estudios han sido muy controversiales. El único estudio prospectivo fue realizado por McGuire y cols.…”
Section: Discussionunclassified
“…y Shore y cols., en 2014 y 2015 respectivamente, mostraron que el uso de Prolaris, cambió la conducta del tratamiento, evidenciando una importante reducción en manejo con intención curativa, 49,5% de cirugía, 29,6% de radioterapia en el estudio de Shore y un cambio en la conducta de tratamiento 47,8%, incluyendo tanto cirugía como radioterapia, en el estudio de Crawford. 13,14 En cuanto a los alelos de riesgo para cáncer de próstata, los resultados entre los diferentes estudios han sido muy controversiales. El único estudio prospectivo fue realizado por McGuire y cols.…”
Section: Discussionunclassified
“…A biopsybased registry study reported 13% of patients with cancer that was less aggressive than expected changed from nonintervention to intervention, whereas 11% of patients with disease that was more aggressive than expected changed from intervention to nonintervention. 21 A substantial proportion of participants (15%) in this analysis were African American, a population group that experiences significant health disparities in terms of PCa treatments and outcomes. 22 Some experts have cited evidence of higher rates of upgrading at surgery 23 and progression 24 on AS to suggest that noninterventional strategies should be considered selectively in African-American men.…”
Section: Commentmentioning
confidence: 98%
“…Thus far, analysis of these registries is suggesting a change in treatment recommendations in 47-65% of patients based on biopsy derived CCP scores. [67, 68] Ongoing evaluation will be required to demonstrate the accuracy of these recommendations and demonstrate utility in the post-prostatectomy setting.…”
Section: Currently Available Testsmentioning
confidence: 99%